Indicators of Production and Economic Efficiency of Adding Premix to the Diet of Friesian Cows - Dabdoub, Sumaia; Alhajomar, Omar (Jordan Journal of Agricultural Sciences, 2024)
The research aims to study the effect of adding premix to the diet on the amount of milk produced during the summer and winter months and thus to study the interaction between the premix and the milking seasons at different ages in Friesian cows. The study was conducted at the Mokhtariya station on 30 cows over six months in 2022. The experimental animals were distributed into three different and uniform ages in each season, cows aged (3, 5, and 7) years and from the first, third, and fifth milking seasons, and different amounts of premix were added ( 1-0.50-0.25) g/kg to the feed during the summer and winter seasons. The results showed, for example, that the average milk production using the 1 g/kg premix is 4.32 kg more than 0.25 g/kg, and 5.815 kg more than 0.5 g/kg. It was also shown that the average milk production using the 1 g premix /kg in winter exceeds 0.25 g/kg and 0.5 g/kg by about 4.37 kg and 7.407 kg for each, respectively. About economic indicators, for example, 3-year-old cows showed Results: The lowest value of total revenues was estimated at 61.9 thousand SYP for the amount of premix (0.25 g/kg), compared to its maximum value, which was estimated at 115.4 thousand SYP for the amount of premix (1 g/kg), in the summer. The study recommended adding premix to dairy cows' diets in an amount of (1) g/kg.